2002
DOI: 10.1086/339583
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Protective Immunity by SyntheticVibrio choleraeHexasaccharide Derived fromV. choleraeO1 Ogawa Lipopolysaccharide Bound to a Protein Carrier

Abstract: Synthetic antigens that mimic the terminal hexasaccharide epitope of the O-specific polysaccharide of Vibrio cholerae O1, serotype Ogawa, were conjugated to bovine serum albumin (BSA). Conjugates with carbohydrate-to-carrier molar ratios of 15.5:1, 9.2:1, and 4.6:1 were tested for immunogenicity and efficacy in mice. The role of preimmunity to BSA and the use of adjuvant in the generation of the serologic response to the O-specific polysaccharide and protection against virulent V. cholerae was examined. Preimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 44 publications
0
116
0
Order By: Relevance
“…These acellular vaccines were introduced into clinical practice in the United States in 1991 as the fourth and fifth doses of a five-dose series and were approved for use in the primary series in 1996 as part of the diphtheriatetanus-acellular pertussis combination vaccine. In addition to reducing the number of adverse events associated with pertussis vaccination, these formulations also proved to be at least as protective as their whole-cell predecessor (7,(12)(13)(14)(15)28). Recent studies have demonstrated that humans are capable of mounting an immune response to TcpF during V. cholerae infection, further validating the hypothesis that TcpF is a viable option for inclusion in a multisubunit cholera vaccine (16).…”
Section: Vol 73 2005mentioning
confidence: 84%
See 2 more Smart Citations
“…These acellular vaccines were introduced into clinical practice in the United States in 1991 as the fourth and fifth doses of a five-dose series and were approved for use in the primary series in 1996 as part of the diphtheriatetanus-acellular pertussis combination vaccine. In addition to reducing the number of adverse events associated with pertussis vaccination, these formulations also proved to be at least as protective as their whole-cell predecessor (7,(12)(13)(14)(15)28). Recent studies have demonstrated that humans are capable of mounting an immune response to TcpF during V. cholerae infection, further validating the hypothesis that TcpF is a viable option for inclusion in a multisubunit cholera vaccine (16).…”
Section: Vol 73 2005mentioning
confidence: 84%
“…These results may have been in part related to differential expression of antigens that engender protective immunity. Several studies have documented the efficacy of antibodies directed against V. cholerae subunits (TcpA and lipopolysaccharide) for protection from disease in the infant mouse cholera model (7,28,38,39,52). Subunit vaccines may prove to be superior to whole-cell live vaccines since the appropriate antigens can reliably be introduced into each individual at the appropriate dose.…”
Section: Vol 73 2005mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the problems associated with LPS, synthetic O-SP sugar components can be conjugated to protein carriers (neoglycoconjugates) to recruit T cells. Although Ogawa neoglycoconjugates induced protective antibodies in mice (Chernyak et al, 2002), Inaba neoglycoconjugates induced only low-affinity antibodies that were not protective. This may be due to low intrinsic affinity of the epitope for Inaba-specific B-cell receptor.…”
Section: Introductionmentioning
confidence: 92%
“…Of note, Wu et al (42) also found protection to occur in offspring of dams immunized parenterally with a TcpA pilin peptide polymer and adjuvant, although there were measurable IgA responses in vaccinated dams in this experiment. Also, a number of researchers have assayed protection in neonatal mice by using passively administered convalescent-phase sera from immunized and unrelated adult mice (the neonates were, therefore, not ingesting breast milk of immunized dams, suggesting that protection was present in the serum fraction) (2,5). In the latter experiments, convalescent-phase sera of immunized animals were mixed with the V. cholerae challenge inoculum prior to oral administration to neonates.…”
Section: Vol 74 2006mentioning
confidence: 99%